(untitled) - Fenn, Janice (San Francisco, 2005)
Do You See What I See? offers leaders, managers, and human resource professionals a unique and practical resource for understanding the behavioral subtleties and nuances that affect the retention of people of color within organizations. Through the imaginative use of a fable, authors Janice Fenn and Chandra G. Irvin are able to show different points of view of leaders, managers, and newly recruited POC. In the fable a mirror comes to life and offers insightful reflections that help executives and managers understand what it takes to retain POC in a highly competitive marketplace. Step by step the authors clearly show what happened, what should have happened, conclusions that were drawn, and conclusions that should have been drawn. The fable offers the opportunity for leaders and managers to identify and address similar issues in their real life organizations.
Keywords: Diversity in the workplace,Employee retention,Sự đa dạng nơi làm việc,Giữ nhân viên